Communicating With School Nurses About Sexual Orientation and Sexual Health: Perspectives of Teen Young Men Who Have Sex With Men. (October 2015) - Rasberry, Catherine N.; Morris, Elana; Lesesne, Catherine A.; Kroupa, Elizabeth; Topete, Pablo; Carver, Lisa H.; Robin, Leah
Black and Latino young men who have sex with men (YMSM) are at disproportionate risk for sexually transmitted diseases (STDs), including HIV. This study informs school-centered strategies for connecting YMSM to health services by describing their willingness, perceived safety, and experiences in talking to school staff about sexual health. Cross-sectional data were collected from Black and Latino YMSM aged 13–19 through web-based questionnaires ( N = 415) and interviews ( N = 32). School nurses were the staff members youth most often reported willingness to talk to about HIV testing (37.8%), STD testing (37.1%), or condoms (37.3%), but least often reported as safe to talk to about attraction to other guys (11.4%). Interviews revealed youth reluctance to talk with school staff including nurses when uncertain of staff members' perceptions of lesbian, gay, bisexual, transgender, and questioning (LGBTQ) people or perceiving staff to lack knowledge of LGBTQ issues, communities, or resources. Nurses may need additional training to effectively reach Black and Latino YMSM.